Inverse correlation between serum albumin and serum lactate in adults with dengue - Mauleti, Ifael Yerosias; Suhendro, Suhendro; Nainggolan, Leonard; Rumende, Martin (Faculty of Medicine, Trisakti University, 2016)
BACKGROUNDDengue infection is an acute viral infection, in the natural history of which plasma leakage may occur, resulting in shock followed by tissue hypoxia, with death as the final outcome if not treated properly. The purpose of this study was to determine the correlation of the hematocrit, serum albumin concentration, and the presence of pleural effusion or ascites, with hyperlactatemia in adult dengue patients.METHODSA cross-sectional study was conducted on 62 subjects. The inclusion criteria were: diagnosed dengue viral infection, age >14 years, fever during three consecutive days, and hyperlactatemia. Serum albumin was measured on an Advia 1800 analyzer using the bromocresol green method. The lactate oxidase method was used to determine serum lactate levels. Pleural effusion and/or ascites was determined using an ultrasound scanner (Xario SSA-660 A, Toshiba, Japan). The Pearson correlation test was used to analyze the data.Â RESULTSThere was no significant correlation between the hematocrit (r=0.11; p=0.301), serum albumin (r=0.003;p=0.981), and pleural effusion or ascites (r=0.75; p=0.692) with serum lactate levels. However, in patients aged >30 years there was a significant inverse correlation between serum albumin and lactate levels (r =- 0.663;p=0.026). CONCLUSIONThis study demonstrated a significant inverse correlation between albumin and serum lactate levels in dengue patients aged > 30 years. This can aid in the early recognition and prompt management of at-risk patients to reduce morbidity and mortality.